Functionalism and World Politics A Study Based on United Nations Programs Financing Economic Development - Sewell, James Patrick (Princeton Legacy Library, 2016)
The International Bank for Reconstruction and Development, the International Finance Corporation, the International Development Association, and the United Nations Special Fund are considered.Originally published in 1966.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905